Scientific collaboration and communication in academic social networks - Cebrián Martín, Daymel Adalberto; Legañoa Ferrá, María de los Ángeles; García Batán, Jorge (Transformación, 2024)
Objective: The current society has witnessed how the role of teachers at the university has been transformed by the impact of ICT. The purpose of this research is to assess the Pedagogical Sciences university teachers’ behavior during a one-year period as scientific communication and collaboration in academic social networks is concerned.Methods: A panel longitudinal study was carried out on a sample of 12 researchers. Instruments applied for gathering information were the interview and the network profiles observation.Results: A conceptualization of scientific communication and collaboration processes in academic social networks was an outcome. The main finding of this research shows that researchers are reluctant to share resources and to contribute with their knowledge to other academician's researches in digital environments. Another relevant outcome is that academic social networks are used essentially for disseminating information, in paper format preferably.Conclusions: Scientific communication and collaboration in academic social networks are affected fundamentally by two elements: the trend to avoid sharing or requesting information and the inertia to the use of collaborative technologies for researching.
Keywords: university teacher; scientific communication; scientific collaboration; academic social networks; research